2022
DOI: 10.1177/15210251221100415
|View full text |Cite
|
Sign up to set email alerts
|

Student Academic Engagement and Burnout Amidst COVID-19: The Role of Purpose Orientations and Disposition Towards Gratitude in Life

Abstract: The current study considered the role of broad life orientations of university students on their academic engagement and burnout within the context of COVID-19 pandemic. Specifically, the purpose of this study was to examine whether life purpose orientations predicted student academic engagement and burnout directly and indirectly through disposition towards gratitude. University students completed questionnaires assessing academic engagement, burnout (reduced sense of schoolwork accomplishment, schoolwork dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Gratitude is positively linked to a sense of purpose and meaning in life [20,50,51]. Both a disposition towards gratitude and a sense of purpose in life may help to buffer stress-related psychological disturbances caused by COVID-19 [16]. The empirical evidence on differences in the experience of gratitude depending on gender in the vast majority of cases supports this thesis.…”
Section: Crisis Experience Gratitude and Purpose In Lifementioning
confidence: 62%
See 1 more Smart Citation
“…Gratitude is positively linked to a sense of purpose and meaning in life [20,50,51]. Both a disposition towards gratitude and a sense of purpose in life may help to buffer stress-related psychological disturbances caused by COVID-19 [16]. The empirical evidence on differences in the experience of gratitude depending on gender in the vast majority of cases supports this thesis.…”
Section: Crisis Experience Gratitude and Purpose In Lifementioning
confidence: 62%
“…Meaning in life is the strongest human motivator [14]. Purpose in life is positively related to good health, quality of life, and well-being [15,16]. Life satisfaction, hope, optimism, coping, and well-being can lead to an increase in one's sense of purpose in life [17][18][19].…”
Section: The Relationship Between the Crisis Experience And Purpose I...mentioning
confidence: 99%
“…Extensive research has been conducted on the proactive, even preventive, effects of gratitude on reducing burnout in a wide variety of professions including medical teams, athletes, and students (Camero & Carrico, 2022;Ruser et al, 2020;Yukhymenko-Lescroart, 2022). For instance, a study by Guan and Jepsen (2020) identified gratitude as a positive resource for healthcare teams, buffering the effects of cognitive overload on emotional exhaustion and the effects of response modulation on emotional exhaustion and depersonalization.…”
Section: Gratitudementioning
confidence: 99%
“…This seems to be negatively associated with academic burnout and correlated with low academic engagement and loneliness, even before the COVID-19 pandemic. These factors were worse during the COVID-19 pandemic, when the social isolation force the loneliness became more frequent since the support from friends and the academic community shifted predominantly to online chats and meetings (Caesens et al, 2014;Galdino et al, 2016;Gewin, 2021;Naumann et al, 2022;Peltonen et al, 2017;Singh et al, 2020;Yukhymenko-Lescroart, 2022).…”
Section: Graduate Student Burnoutmentioning
confidence: 99%